A Low-Power, Auto-DC-Suppressed Photoplethysmography Readout System with Differential Current Mirrors and Wide Common-Mode Input Range Successive Approximation Register Analog-to-Digital Converter - Chanyoung Son; Seok-Tae Koh; Hyuntak Jeon (Micromachines)
This paper presents a low-power photoplethysmography (PPG) readout system designed for wearable health monitoring. The system employs a differential current mirror (DCM) to convert single-ended PPG currents into differential voltages, inherently suppressing DC components. A wide common-mode input range (WCMIR) SAR ADC processes the differential signals, ensuring accurate analog-to-digital conversion. The DCM eliminates the need for DC cancelation loops, simplifying the design and reducing power consumption. Implemented in a 0.18 µm CMOS process, the system occupies only 0.30 mm2, making it suitable for multi-channel applications. The system achieves over 60 dB DC dynamic range and consumes only 9.6 µW, demonstrating its efficiency for portable devices. The simulation results validate its ability to process PPG signals across various conditions, offering a scalable solution for advanced biomedical sensing platforms.